A resilience lens to explore seaweed farmers' responses to the impacts of climate change in Tanzania. Issue 1 (31st December 2022) - Matoju, Ivy; Le Masson, Virginie; Montalescot, Valeria; Ndawala, Msafiri Andrew; Msuya, Flower E.
ABSTRACT: Seaweed-based mariculture is an important source of livelihoods for impoverished coastal communities in Tanzania. However, the impacts of climate change across East Africa are putting a strain on the growth of the seaweed industry. Smallholder farmers are already mobilizing strategies to cope with challenges such as disease outbreaks, but they are struggling to maintain seaweed production and derive sufficient income. A better understanding of the challenges they face and the factors inhibiting their ability to build resilience is needed to inform policies and development programmes to achieve the Sustainable Development Goals, particularly Goal 13 on Climate action and Goal 14 on Life Below Water. The global demand for seaweed is expanding rapidly. Strengthening the adaptability of seaweed production to climate change is important for farmers to rely on it as a source of livelihoods on which they can build their own resilience to climate change. Drawing on qualitative data from key informant interviews in four Tanzanian seaweed-producing areas, this paper assesses the long-term resilience capacities of seaweed farmers to respond to one of the main hazards: diseases affecting seaweed crops. While several strategies help farmers maintain their income, most of them only support resilience in the short term. The increasing pressure on marine resources and the lack of regulations for supporting an equitable and sustainable seaweed-based mariculture sector do not bode well for farmers' long-term adaptation to climate change and environmental degradation. Seaweed farming remains a crucial source of livelihoods for poor coastal communities in Tanzania, but it does not currently lead to positive transformative changes in their socio-economic conditions. Policies aiming to support sustainable aquaculture, particularly in tropical ecosystems that are highly vulnerable to climate change, must address the existing social, economic and knowledge inequities that prevent poor communities from building their resilience.